POTENSI EKSTRAK ETANOL DAUN BELIMBING WULUH (Averrhoa bilimbi L.) SEBAGAI ANTIBAKTERI TERHADAP Staphylococcus haemolyticus - Egedius Harley Johandi; Muh. Taufiqurrahman; Risny Risny (Unit Penelitian dan Pengabdian Kepada Masyarakat (UPPM) STIKES Dirgahayu Samarinda, 2025)
Antibacterial activity of ethanol extract of starfruit leaves (Averrhoa bilimbi L.) against Staphylococcus haemolyticus. Background highlights the growing concern over antibiotic resistance, which poses significant health risks at both the individual and societal levels. This study aims to explore natural alternatives to antibiotic treatment, leveraging the traditional use of natural ingredients in medicine. This study will employ a systematic approach, including the extraction of active compounds from the leaves using a maceration method with 96% ethanol as a solvent. The study will also assess the presence of bioactive compounds such as triterpenoids, known for their pharmacological properties, including antibacterial effects. The research question focuses on determining the antibacterial efficacy of the extract and categorizing the degree of inhibition based on varying concentrations. These findings are expected to contribute to the understanding of natural remedies in combating bacterial infections and may pave the way for future drug development based on plant-derived compounds. This proposal examines the antibacterial activity of ethanol extract of starfruit leaves (Averrhoa bilimbi L.) against Staphylococcus haemolyticus as a natural alternative to address antibiotic resistance. The maceration method is used to extract bioactive compounds such as triterpenoids. This study evaluated the antibacterial effectiveness at various concentrations and is expected to support the development of plant-based medicines.